The impact of aquatic training program for the development of some physical quality of the handballplayers under 17 years - رشيد , أمان الله; hamid mansour, azzizi zakaria (Journal of Sport Science Technology and Physical Activities, 2025)
The study aims to propose an aquatic training program for the development of some physical quality of the handballplayers under 17 yearsusing the experimental design of the control and experimental groups and after determining the original community of the study, which is represented in the handball players of the sport Club Wifak Tissemsilt Due to the nature of the research, we applied the experimental method, and the sample was chosen in a deliberate manner, which amounted to 26 players, having the same specifications, age, height, weight. The team was divided into two groups 09 control Individuals and 09 experimental Individuals We applied a set of physical tests and the suggested aquatic training program according to the experimental group normal manner, there were significant statistical differences between the control group and the experimental group in favor of the proposed aquatic educational program